Optimizing oral 3-hydroxybutyrate dosage using pharmacokinetic model to improve cognitive function and mood in healthy subjects - Nishioka, Kentaro; Ishimoto, Takahiro; Sato, Mariko; Yasuda, Ruki; Nakamura, Yumi; Watanabe, Hiroshi; Suzuki, Toshihide; Araragi, Yudai; Kato, Yukio; Yoshida, Ken-ichi; Murayama, Norihito (Frontiers in Nutrition, 2025)
IntroductionThe brain uses ketones, mainly 3-hydroxybutyrate (3-HB), as an alternative energy source. Therefore, oral intake of 3-HB may help maintain brain health. Previous studies indicated that achieving a maximum concentration (Cmax) of 3-HB in plasma at 0.28 mM could initiate ketone metabolism in the brain; we hypothesized that attaining this Cmax would improve brain health.MethodsWe aimed to demonstrate the efficacy of an optimized single oral dose of 3-HB on cognitive function and mood through two clinical studies: a pharmacokinetic study and an efficacy study. In the pharmacokinetic study, healthy subjects were ingested 2 and 4 g of 3-HB to construct a compartment model to predict the minimum oral dose of 3-HB needed to achieve the target Cmax. In the efficacy study, a randomized, double-blinded, and placebo-controlled crossover trial, the effects of 3-HB at the predicted doses on cognitive function and mood in healthy subjects were assessed by a serial arithmetic test (SAT), the cognitrax, the profile of mood states 2nd edition (POMS2), and fatigue visual analog scale (VAS).ResultsIn the pharmacokinetic study, a one-compartment model that includes saturable and non-saturable absorption pathways, constant biosynthesis, and the linear elimination of 3-HB after oral administration were constructed. The model principally reflected the observed serum 3-HB concentrations profiles and predicted a minimum dose of 3.5 g needed to achieve the target Cmax. In the efficacy study, although no significant difference was observed in any cognitive domains assessed by the Cognitrax, total responses and correct answers in the SAT were significantly improved in the active group receiving 3.5 g of 3-HB compared to the placebo group. Regarding the POMS2, confusion–bewilderment, fatigue–inertia, vigor-activity, and total mood disturbance scales were significantly improved in the active group compared to the placebo group. Additionally, fatigue VAS were also significantly improved in the active group compared to the placebo group.DiscussionWe successfully established a one-compartment model for oral 3-HB intake and demonstrated partial efficacy on cognitive function and broad efficacy on mood in healthy subjects with a single oral dose of 3.5 g of 3-HB optimized by the model.Clinical trial registrationhttps://www.umin.ac.jp/ctr/index-j.htm, identifier [UMIN000042095, UMIN000046666].